Evaluation of encapsulation and droplet vitrification methods in gene preservation work - Nukari, Anna; Wang, Qiaochun; Uosukainen, Marjatta; Laamanen, Jaana; Rokka, Veli-Matti; Rantala, Saija; Valkonen, Jari (MTT, 2008)
At MTT Nursery Group we were looking for a suitable cryopreservation procedure that could be applicable for a wide range of species and genotypes. Different techniques for the cryopreservation of raspberry were evaluated at the University of Helsinki. Encapsulation was combined with vitrification or used together with dehydration methods (3). At MTT we started the work by combining the vitrification with encapsulation according to the studies of Dr. Wang, but encapsulation was not compulsory for raspberry. Instead of encapsulation-vitrification we started to use our own modified droplet vitrification method for conservation of raspberries and also other vegetatively propagated plants like strawberry. In the long term gene preservation of vegetatively propagated plants and especially as we are using in vitro grown meristems, it is optimal to preserve healthy plant material free of viruses and phytoplasmas (5, 6). Therefore, application of cryotherapy is a practical tool for producing healthy propagation material, that later on can be transferred into long-term preservation using cryopreservation methods (2). In cryopreservation the focus is on conserving plant material in high amounts using such techniques that the survival after thawing is optimal. In cryotherapy however, the focus is not on high survival of plant cells. Instead, it is essential that the viability is conserved, but only the meristem cells are viable after cryopreservation and a minimun amount of the surrounding tissues survive (3). Cryotherapy is more efficient than the traditional virus eradication methods like meristem culture or thermotherapy that were introduced to Finnish raspberry and potato production already in the 70s. Combining cryotherapy with preceding thermotherapy was the solution also in the case of the raspberry bushy dwarf virus, that had earlier been practically impossible to eradicate from the diseased tissues with the traditional methods. Cryopreservation of somatic embryos is potentially a method to cryopreserve increased amounts of accessions. In our project we have tested the methods to produce somatic embryos with several potato and two raspberry cultivars and cryopreservation of the somatic embryos using the encapsulation technique will be studied as the next step. As the conclusion these methods are compatible with each others and we can use them in the Finnish gene preservation work (1). The basic cryopreservation methods are quite practical and effective, but the adaptability of one technique can be more suited for a particular purpose than the adaptability of the other techniques. In cryotherapy and cryopreservation of somatic embryos, encapsulation is especially useful. In large scale preservation the droplet vitrification method is more applicable as a working method.
Keywords: Ka; cryotherapy; potato; raspberry; somatic embryos